2020
DOI: 10.1111/jcpt.13118
|View full text |Cite
|
Sign up to set email alerts
|

Is the interstitial lung disease induced by trastuzumab? Case report and literature review

Abstract: What is known and objective Interstitial lung disease (ILD) is a rare but life‐threatening adverse event (AE) that can be induced by trastuzumab in patients with breast cancer. ILD is a known AE associated with trastuzumab therapy, but it has other causes. We describe a case of ILD, which was induced by Epstein‐Barr virus (EBV). Case summary A 76‐year‐old female patient with early‐stage HER‐2‐positive breast cancer presented with ILD after 10 cycles of trastuzumab and paclitaxel. After excluding the possibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…A precise diagnosis remains challenging especially when confounders of infectious diseases are present. Previous research suggested that infection caused DPLD or co-infections following original DPLD are the common factors that trigger acute exacerbation of the disease ( Vanfleteren and Linssen, 2010 ; Collard et al., 2016 ; Ye et al., 2020 ). Moreover, infections may play a considerable role in the complex interaction between a susceptible host and the environment, leading to the development or progression of interstitial lung disease (ILD) ( Azadeh et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…A precise diagnosis remains challenging especially when confounders of infectious diseases are present. Previous research suggested that infection caused DPLD or co-infections following original DPLD are the common factors that trigger acute exacerbation of the disease ( Vanfleteren and Linssen, 2010 ; Collard et al., 2016 ; Ye et al., 2020 ). Moreover, infections may play a considerable role in the complex interaction between a susceptible host and the environment, leading to the development or progression of interstitial lung disease (ILD) ( Azadeh et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%